Robotic prostatectomy after abandoned open radical prostatectomy—Technical aspects and outcomes. Issue 5 (30th August 2020) - O'Connor, E.; Koschel, S.; Bagguley, D.; Sathianathen, N. J.; Cumberbatch, M. G.; Thangasamy, I. A.; Moon, D.; Murphy, D. G.
Abstract: Objective: To describe the technical aspects and outcomes of robotic‐assisted radical prostatectomy (RARP) following abandoned open radical prostatectomy (ORP). Patients and Methods: A retrospective review was performed of patients who underwent RARP following abandonment of ORP between 2016 and 2020. RARP was undertaken by two highly experienced robotic surgeons. Analysis of patient and operative characteristics, outcomes, and reasons for abandonment of ORP were described. Results: Six patients were included for analysis with a median age of 63.5 years [50.3‐67.5]. The median body mass index (BMI) was 34.7 [27.8‐36.2]. All patients had intermediate‐risk prostate cancer. Small prostate and deep pelvis were given as reasons for abandoning ORP in five cases (83.3%), with four of these also attributing increased BMI as a factor. Extensive mesh from previous bilateral inguinal hernia repair was cited as the reason for abandonment in the remaining patient. One patient had commenced androgen deprivation therapy following abandoned ORP. Extensive retropubic adhesions were noted at the time of RARP in five of six patients, with intraoperative complication of small bladder lacerations encountered in the patient with prior mesh hernia repair. The median time from abandoned ORP to RARP was 128 days [40‐216]. Median operating time was 160 minutes [139‐190] and estimated blood loss was 225 mL [138‐375]. Negative margins were obtained in four of six cases, with further salvage treatment being required in one case at a median follow‐up duration of 10.5 months [6.5‐25.3]. Conclusion: Abandonment of ORP is an uncommonly reported event, however, in this small case series, we demonstrate that, in the hands of experienced surgeons, RARP is a safe and technically feasible alternative in such cases. Increased BMI, small prostate size and pelvic anatomical constraints appear to be common catalysts for abandonment of open surgery in this cohort. Identifying these high‐risk patients early and considering referral to robotic centers may be preferred.